2018
DOI: 10.1152/japplphysiol.00474.2017
|View full text |Cite|
|
Sign up to set email alerts
|

AltitudeOmics: effect of reduced barometric pressure on detection of intrapulmonary shunt, pulmonary gas exchange efficiency, and total pulmonary resistance

Abstract: Blood flow through intrapulmonary arteriovenous anastomoses (Q) occurs in healthy humans at rest and during exercise when breathing hypoxic gas mixtures at sea level and may be a source of right-to-left shunt. However, at high altitudes, Q is reduced compared with sea level, as detected using transthoracic saline contrast echocardiography (TTSCE). It remains unknown whether the reduction in Q (i.e., lower bubble scores) at high altitude is due to a reduction in bubble stability resulting from the lower baromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
2
6
0
Order By: Relevance
“…In hypobaria, the putative increased physiological dead space and altered alveolo‐capillary diffusion in HH compared to NH (Millet et al, ). The present results of trueV˙E (10.3 vs. 12.1 L/min in HN vs. NN) are in line with previous values in HN versus NN at rest (11.5 vs. 15.6 L/min) (Petrassi et al, ). The lower P ET CO 2 in HN versus NN was observed in the three phases (baseline, hyperventilation, and hypercapnia) without any hyperventilation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In hypobaria, the putative increased physiological dead space and altered alveolo‐capillary diffusion in HH compared to NH (Millet et al, ). The present results of trueV˙E (10.3 vs. 12.1 L/min in HN vs. NN) are in line with previous values in HN versus NN at rest (11.5 vs. 15.6 L/min) (Petrassi et al, ). The lower P ET CO 2 in HN versus NN was observed in the three phases (baseline, hyperventilation, and hypercapnia) without any hyperventilation.…”
Section: Discussionsupporting
confidence: 94%
“…Decrease in barometric pressure has been reported to also increase pulmonary vascular vasoconstriction pressure due to the lower air density in hypobaria (Conkin, ). More precisely, pulmonary resistance was increased in hypobaria (HN and HH), independent of oxygen tension, suggesting that pulmonary blood flow may be changed in hypobaria (Petrassi et al, ). Moreover, different fluid and acid–base balance responses mediated by augmentation of aldosterone and altered cell‐membrane permeability have been suggested as a consequence of hypobaria (Loeppky et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, below a PnormalAO2 of ∼70 Torr the contribution of a diffusion limitation would increase and the normalAnormal-normalaDO2 would begin to widen, or would be similar to the normalAnormal-normalaDO2 under resting normoxia, depending on the level of PnormalAO2. This is precisely what the present data and previous work (Eldridge, Braun, Yoneda, & Walby, 2006; Elliott et al., 2015; Farrell et al., 2015; Jonk et al., 2007; Petrassi et al., 2018; Podolsky et al., 1996) demonstrate and is parallel to what was proposed by the modelling work of Farhi and Rahn (1955).…”
Section: Discussionsupporting
confidence: 85%
“…Many studies have examined differences in hypobaric and normobaric hypoxia to determine whether hypoxia per se is causing the physiological changes observed, or whether reductions in barometric pressure combined with hypoxia result in the observed physiological alterations. While there is still considerable debate in this area (Millet et al., 2012; Mounier & Brugniaux, 2012), multiple studies have shown many different responses to hypobaric hypoxia compared to normobaric hypoxia despite identical PInormalO2${P_{{\rm{I}}{{\rm{O}}_{\rm{2}}}}}$, PanormalO2${P_{{\rm{a}}{{\rm{O}}_{\rm{2}}}}}$ and PAnormalO2${P_{{\rm{A}}{{\rm{O}}_{\rm{2}}}}}$ between conditions (Aebi et al., 2020; Beidleman et al., 2014; Coppel et al., 2015; Faiss et al., 2013; Loeppky et al., 1997, 2005; Petrassi et al, 2018; Roach et al., 1996; Saugy et al., 2016; Savourey et al., 2003; Takezawa et al., 2021; Woods et al., 2017). For example, SanormalO2${S_{{\rm{a}}{{\rm{O}}_{\rm{2}}}}}$ and trueV̇normalE${\dot{V}_{\rm{E}}}$ are lower during short term exposure to hypobaric hypoxia compared to normobaric hypoxia (Loeppky et al., 1997; Savourey et al., 2003).…”
Section: Discussionmentioning
confidence: 99%